Street 21 Meatball / Md. Zulfadhli Badaruddin... [et al.] - Mansur, Suhaibah; Datu Wasladi, Dayang Darwisa; Qasimudin, Suri Lamlai; Badaruddin, Md. Zulfadhli (2014)
Nowadays, there are several business existed in our country which compete each other. Entrepreneurship acts as the movers of the economy who involved in the business of products or services. However, the entrepreneurship have absolute right to make decision what product to be produce based on relevancy. Business might be given profit or gain losses but it depends on the entrepreneurship manage the business as well. Normally, entrepreneurship opens up business because want to get maximum profit. After we made some decision, we determined to serve a variety of meatball as our product. Before we made this decision, we already did various methods to identify the chance in the business field. Nevertheless, our company name is STREET2 1 meatball which established as partners' company. We will start our company on 06 JUNE 20 15. We confident to run in this business field where we can gain our business target. Our priority is to make sure a very friendly customer service and customer satisfaction .This kind of business has a good opportunity to gain profit and contribute to the economic development of our country. We come with variety ingredient which we make it ourselves. In our business, we will put a priority on the quality of the product and services as well as the costumer's satisfaction. Our target market helps us in producing product where we are focus in Kota Kinabalu as our first step before expand our company. We use several methods to get important information from various resources. There are through interview and our observations about society demands. The result helps us making in marketing analysis about our market size, determining our main competitors, the sales forecast and the marketing strategies.